Alcoholic anonymous in the world and in Turkey - Yıldız, Abdullah (Journal of Dependence, 2021)
Self-support groups have an important role in different dimensions in the treatment of alcohol dependence. The best known of these groups is the Alcoholics Anonymous (AA). In this study, the historical development, philosophy and important concepts of anonymous alcoholics are explained and their relationship with psychiatry is mentioned. However, it is thought that it is important to make a short introduction to the history of Alcohol and Alcohol Addiction in terms of determining the place and importance of the AA group in the historical process. The literature on alcohol, alcohol addiction and AA has been reviewed from a medical history perspective. Historical findings on alcohol addiction date back to antiquity. The relationship between the modern concept of alcohol addiction and medicine is parallel with the development of modern psychiatry. At the beginning of the 20th century, it is seen that religious groups are active in alcohol addiction. While AA took a different approach in this process, it gained a privileged place. Since the middle of the 20th century, it has been in interaction with modern medicine and psychiatry and has made important contributions to addiction. The development of AA in Turkey is relatively new and has encouraged the establishment of other groups. In conclusion, AA has a historically important place in the development of alcohol addiction treatment. The group’s philosophical orientation and its relationships with addiction psychiatry have been important in this context.